3D osteoarthritic changes in TMJ condylar morphology correlates with specific systemic and local biomarkers of disease - Cevidanes, L. H. S.; Walker, D.; Schilling, J.; Sugai, J.; Giannobile, W.; Paniagua, B.; Benavides, E.; Zhu, H.; Marron, J. S.; Jung, B. T.; Baranowski, D.; Rhodes, J.; et al. (Elsevier B.V., 2014)
Objective: To assess 3D morphological variations and local and systemic biomarker profiles in subjects with a diagnosis of temporomandibular joint osteoarthritis (TMJ OA).Design: Twenty-eight patients with long-term TMJ OA (39.9 +/- 16 years), 12 patients at initial diagnosis of OA (47.4 +/- 16.1 years), and 12 healthy controls (41.8 +/- 12.2 years) were recruited. All patients were female and had cone beam CT scans taken. TMJ arthrocentesis and venipuncture were performed on 12 OA and 12 age-matched healthy controls. Serum and synovial fluid levels of 50 biomarkers of arthritic inflammation were quantified by protein microarrays. Shape Analysis MANCOVA tested statistical correlations between biomarker levels and variations in condylar morphology.Results: Compared with healthy controls, the OA average condyle was significantly smaller in all dimensions except its anterior surface, with areas indicative of bone resorption along the articular surface, particularly in the lateral pole. Synovial fluid levels of ANG, GDF15, TIMP-1, CXCL16, MMP-3 and MMP-7 were significantly correlated with bone apposition of the condylar anterior surface. Serum levels of ENA-78, MMP-3, PAI-1, VE-Cadherin, VEGF, GM-CSF, TGF beta b1, IFN gamma g, TNF alpha a, IL-1 alpha a, and IL-6 were significantly correlated with flattening of the lateral pole. Expression levels of ANG were significantly correlated with the articular morphology in healthy controls.Conclusions: Bone resorption at the articular surface, particularly at the lateral pole was statistically significant at initial diagnosis of TMJ OA. Synovial fluid levels of ANG, GDF15, TIMP-1, CXCL16, MMP-3 and MMP-7 were correlated with bone apposition. Serum levels of ENA-78, MMP-3, PAI-1, VE-Cadherin, VEGF, GM-CSF, TGF beta 1, IFN gamma, TNF alpha, IL-1 alpha, and IL-6 were correlated with bone resorption. Published by Elsevier Ltd on behalf of Osteoarthritis Research Society International.
Keywords: Imaging biomarkers; Protein biomarkers; Image analysis